You shouldn't have come here [large type] - Rose, Jeneva (Blackstone Publishing, 2023)
Overworked city gal Grace Evans is ready for a relaxing getaway on a Wyoming ranch, where the owner is handsome Calvin Wells. But when she hears of a missing woman, things soon change for the worse.